The Influence of Ability, Work Discipline, and Work Motivation on Employee Performance (Study on Honorary Employees at the Department of Transportation of the City of Binjai) - Dita Selvioneta Yuni Siahaan; Yohny Anwar; Husni Muharram Ritonga (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
This research was conducted to find the effect of ability, work discipline, and work motivation on the performance of honorary employees at the Department of Transportation of Binjai City. The population in this research amounted to 45 honorary employees. The number of samples also took as many as 45 honorary employees as respondents. The sampling technique used was saturated sampling. This research used primary data in the type of quantitative data collected through questionnaires and processed using the SPSS 24.0 application. The research was conducted from September 2021 - February 2022. The analytical technique used was using multiple linear regression models. The results showed that the ability, work discipline, and work motivation both partially and simultaneously had a positive and significant effect on the performance of honorary employees at the Department of Transportation of Binjai City. The most dominant variable affecting the performance of honorary employees was the work motivation variable with the largest tcount of 3,715. In addition, 87.8% of employee performance can be explained and obtained from ability, work discipline, and work motivation, while the rest was obtained from other factors. Employee performance has a very strong relationship to ability, work discipline, and work motivation.